Disease Pattern and Its Association with Outcome of Bubble CPAP in Neonates with Respiratory Distress Who Received Bubble CPAP (The Planet, 2023)
Background: Respiratory distress arises in 0.96-12% oflife birth and is accountable for about 20% of newbornmortality and is the most usual presenting complaint ofnewborn encountered within the first 48-72 hours of lifeand remains the main indication for admission to neonatalintensive care unit to combat respiratory failure. Methodsand Materials: This cross-sectional study was conductedin the neonatal intensive care unit, Bangladesh ShishuHospital & Institute from April 2017 to June 2017 with atotal of fifty-two neonates with respiratory distress. Result:Among the study patients most of the neonates (46.1%)belonged to age ≤24 hours. It was observed that forty-ninepatients (94.2%) had chest retraction followed by forty-one(78.8%) had tachypnoea, about half (52.0%) had cyanosis,twenty-five (48.0%) had H/O apnoea and twenty (38.4%)had pallor. Of the neonates with respiratory distress which needed Bubble CPAP supportnine (17.3%) had RDS, nine (17.3%) had PNA, seven (13.5%) had pneumonia, seven (13.5%)had PPHN, five had (9.6%) sepsis, and two had (4.0%) Laryngomalacia. More than threefourth of the patients (78.8%) were found successfully weaned and one-fifth of the patients(21.2%) were found failed. Out of eleven failure cases who were put into mechanicalventilator, eight cases (72.7%) died and three (27.3%) cases survived and got discharge.Conclusion: This current study concluded that Bubble CPAP is an effective way ofimproving oxygenation of neonates with respiratory distress due to numerous reasons. Sepsisand PPHN has significant relation with Bubble CPAP failure.
Keywords: Respiratory Distress; Neonates; Bubble CPAP